Rola ustawy z dnia 12 X 1994 r. w ochronie obrotu gospodarczego - Tobis, Aleksander (Wydział Prawa i Administracji UAM, 1995)
The paper focuses on the role of the bill of 12 October 1994 (Journal of Laws no 126 item 615) on the protection through penal law of economic turnover in Poland. In particular, principles regulating new types of crimes and offences such as property damages caused to an individual or a company, abuse of confidence, obtaining, on false pretences, of a bank loan, loan guarantee, grant, subsidy or other public funds etc. The construction of the offences relating to false pretences has been compared with those of the crimes of fraud. Further, crimes related to insurance fraud, crimes against creditors and offences leading to a disruption of tender are described. "Money laundering" has been separately discussed. The manner in vhich the bill has been drafted is being criticised and the paper also criticises its legislative methodology. The bill should become an integral part of the new penal code.
The role of the bill of 12 October 1994 in the protection of economic turnover